Parents' Perception of the Impact of Giving Gadgets - selvia novitasari; Ferasinta Ferasinta; Andry Sartika; Leni Rozani (Health and Technology Journal (HTechJ), 2025)
Gadgets are a technology that is developing today, and not only adults but children of different ages have been exposed to them. One of them is in preschool children, parents give gadgets to children so that they can become learning media and parents can do activities without any distractions. Gadgets certainly impact their users depending on how they are used. This study aims to determine parents' perceptions of the impact of giving gadgets to preschool children. This study uses a quantitative research approach. The sample in this study was 32 children. The researcher provided an instrument in the form of a questionnaire regarding parents' perception of gadgets and the impact of giving gadgets to preschool children. The results of this study showed that parents' perception of the impact of giving gadgets to preschool children was mainly in the good category. However, gadgets also hurt children; children become addicted to playing with gadgets. Suggestions can be used as an essential reference in researching the perception and impact of gadget use further and better.